2006
DOI: 10.1002/ab.20170
|View full text |Cite
|
Sign up to set email alerts
|

Insight into illness and adherence to psychotropic medications are separately associated with violence severity in a forensic sample

Abstract: Violence towards others by a minority of psychotic individuals is a significant public health concern. The severity of this otherdirected violence (ODV) in the community may be influenced by insight into illness and adherence to psychotropic medications; however, few studies have tested these associations. Sixty male psychotic inpatients, legally detained at a forensic unit in New York City, were assessed with semi-structured interviews, supplemented with information from hospital and official records, family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 46 publications
3
33
1
2
Order By: Relevance
“…History of childhood physical abuse was one of the factors associated with the occurrence of incidents of assaultive behavior among 183 male patients of a forensic psychiatric hospital, 106 of whom were diagnosed with schizophrenia [30]. A group of 60 male psychotic patients legally detained at a forensic unit was assessed for history of violence; the participants were also asked about any history of childhood abuse, substance use, medication adherence, and current insight in terms of awareness of mental illness [60]. Multiple regression analysis indicated that the history of childhood abuse was associated with the severity of violence independently of substance use, medication adherence, and insight (beta = 0.18, < 0.01) [60].…”
Section: Static Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…History of childhood physical abuse was one of the factors associated with the occurrence of incidents of assaultive behavior among 183 male patients of a forensic psychiatric hospital, 106 of whom were diagnosed with schizophrenia [30]. A group of 60 male psychotic patients legally detained at a forensic unit was assessed for history of violence; the participants were also asked about any history of childhood abuse, substance use, medication adherence, and current insight in terms of awareness of mental illness [60]. Multiple regression analysis indicated that the history of childhood abuse was associated with the severity of violence independently of substance use, medication adherence, and insight (beta = 0.18, < 0.01) [60].…”
Section: Static Factorsmentioning
confidence: 99%
“…A group of 60 male psychotic patients legally detained at a forensic unit was assessed for history of violence; the participants were also asked about any history of childhood abuse, substance use, medication adherence, and current insight in terms of awareness of mental illness [60]. Multiple regression analysis indicated that the history of childhood abuse was associated with the severity of violence independently of substance use, medication adherence, and insight (beta = 0.18, < 0.01) [60]. In a group of 28 schizophrenia patients with a history of violence, 46% had experienced child abuse and/or neglect [61].…”
Section: Static Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…[34,35] Genellikle şizofreninin pozitif bulguları artmış şiddet davranışı ile ilişkilendirilirken, negatif bulguları tersi şekilde ilişkilendirilir. [36] Son olarak, içgörü eksikliği ile şiddet davranışı ilişkisi arasında tutarlılık gösteren kanıtlar mevcuttur. [37][38][39][40] Bu etki içgörü eksikliğinden ötürü düzensiz tedaviye yönelimin sonucunda meydana gelen şiddet davranışı ile ilişkilendirilen dolaylı bir etkidir.…”
Section: Klinik öZelliklerunclassified